Flexibility in the market for international carbon credits and price dynamics difference with European allowances - Claire Gavard; Djamel Kirat (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
The Paris Agreement establishes a mechanism to allow a Party to benefit from greenhouse gases emissions reductions conducted in a host Party to fulfil its nationally determined contribution. In this context, the objective of this paper is to improve the understanding of carbon offsets price dynamics, in comparison with regular carbon markets allowances. We combine a cointegration approach with risk premium considerations to compare the price dynamics of European Union Allowances (EUA) and Certified Emission Reductions (CER) in the second phase of the European carbon market. By taking account of breaks identified in the series, we find that, while the EUA and CER returns present comparable dynamics, the long-term relationships between the price of these two types of permits and their drivers differ significantly. Given the impact of energy prices (positive for coal and negative for gas) on the CER price, we suggest the existence of a supply-side effect for credits. We find that the price elasticity of allowances with regard to the coal and gas prices is negative in time periods of low economic activity and positive in the rest of the time. We explain the latter by the fact that the market is not tight and the former by the effect of the economic activity on the price of commodities and energy.
Keywords: 330; European allowances; international credits; emissions trading; power sector; structural breaks; time series analysis